Photographing Injuries in the Acute Care Setting: Development and Evaluation of a Standardized Protocol for Research, Forensics, and Clinical Practice. (13th April 2016) - Bloemen, Elizabeth M.; Rosen, Tony; Cline Schiroo, Justina A.; Clark, Sunday; Mulcare, Mary R.; Stern, Michael E.; Mysliwiec, Regina; Flomenbaum, Neal E.; Lachs, Mark S.; Hargarten, Stephen
Abstract: Background: Photographing injuries in the acute setting allows for improved documentation as well as assessment by clinicians and others who have not personally examined a patient. This tool is important, particularly for telemedicine, tracking of wound healing, the evaluation of potential abuse, and injury research. Despite this, protocols to ensure standardization of photography in clinical practice, forensics, or research have not been published. In preparation for a study of injury patterns in elder abuse and geriatric falls, our goal was to develop and evaluate a protocol for standardized photography of injuries that may be broadly applied. Methods: We conducted a literature review for techniques and standards in medical, forensic, and legal photography. We developed a novel protocol describing types of photographs and body positioning for eight body regions, including instructional diagrams. We revised it iteratively in consultation with experts in medical photography; forensics; and elder, child, and domestic abuse. The resulting protocol requires a minimum of four photos of each injury at multiple distances with and without a ruler/color guide. To evaluate the protocol's efficacy, multiple research assistants without previous photography experience photographed injuries from a convenience sample of elderly patients presenting to a single large, urban, academic emergency department. A selection of these patients' images were then evaluated in a blinded fashion by four nontreating emergency medicine physicians and the inter‐rater reliability between these physicians was calculated. Results: Among the 131 injuries, from 53 patients, photographed by 18 photographers using this protocol, photographs of 25 injuries (10 bruises, seven lacerations, and eight abrasions) were used to assess characterization of the injury. Physicians' characterizations of the injuries were reliable for the size of the injury (κ = 0.91, 95% confidence interval [CI] = 0.77 to 1.00), side of the body (κ = 0.97, 95% CI = 0.88 to 1.00), precise location of the injury (κ = 0.74, 95% CI = 0.63 = 0.81), and type of abrasion (κ = 0.76, 95% CI = 0.45 to 1.00). The exact shape of the injury (κ = 0.44, 95% CI = 0.17 to 0.51), and the primary color of bruises (κ = 0.37, 95% CI = 0.25 to 0.48) were not as reliably characterized. Conclusions: Standardizing the documentation of injuries with photographs for clinical and research assessment can be conducted by nonprofessional photographers. A photography protocol will ensure that this important mechanism for documentation is optimized.